Diurnal variation of rainfall in the upper catchments of north Bengal rivers - BHATTACHARYA, P. K.; BHATTACHARYYA, S. G. (MAUSAM, 1980)
A study of the diurnal variation of the rainfall during monsoon season, at six selected stations in upper catchment areas of four north Bengal rivers, viz., Teesta, Jaldhaka, Torsa and Raidak has been attempted on the basis of available data for the period from 1971 to 1976. The different patterns of diurnal variation observed have been discussed.